Identification of Atlantic cod (Gadus morhua), ling (Molva molva), and Alaska pollock (Gadus chalcogrammus) by PCR-ELISA using duplex PCR - Taboada, Ledicia; Sánchez, Ana Cristina; Velasco, Amaya; Santaclara, Francisco J.; Pérez Martín, Ricardo Isaac; González Sotelo, Carmen (Journal of Agricultural and Food Chemistry, 2014)
8 páginas, 5 figuras, 5 tablas Species-specific PCR–ELISA assays for the identification of Atlantic cod (Gadus morhua), Alaska pollock (Gadus chalcogrammus), and ling (Molva molva) in food products have been developed. The method, comprising a set of primers common to the first two species, a set of primers for M. molva, and a probe for each species, was designed using ND4 and cytochrome b genes as molecular markers. The sensitivity and selectivity were then determined for each assay. These assays were afterward used to analyze DNA extracted from commercial fish products. The presence of the target species was successfully detected in all analyzed samples, demonstrating the applicability of this method to the analysis of food products. The work was supported by the projects “ GENTRASEA: Genetic traceability of fish products. Rapid methods with DNA hybridization probes ” and “ LABELFISH: Atlantic network on genetic control of fi sh and seafood labelling and traceability ” . The Spanish Ministry of Science and Innovation is gratefully acknowledged for the doctoral fellowship to L.T Peer reviewed